Serviço social e sustentabilidade: uma nova demanda para a profissão - Mendes, Marina Moscovici (2011)
Sustainable development has become more important in today s world stages. This concept arises as an expression of the attempt to establish a mechanism of control in the face of global problems caused mainly by the capitalist mode of production. One of the great merits of sustainability has been, creating analysis and possibilities for different areas of knowledge. This study seeks to demonstrate how social work is positioning itself in relation to the subject, which seems a demand that has emerged since the middle of twentieth century - more specifically - due to the acceleration of the impacts generated by industrial and economic development. How to put into reality all the professions, at least it seems inappropriate for the social worker, as a professional committed to transformation of social justice, gifted with the theory and methodological training and political ethics, to intervene in the reality in which it operates through mediations built next to the subject that meets in his daily work, not taking his place allying himself with those who seek to establish involvement, in order to build practical knowledge and practices for a sustainable society. In this sense, the target of this study was to investigate the approach that Social Service has with the theme of sustainability, with the broad objective to examine which contributions the profession has brought forward to this question, especially in regards to the social support of sustainability. The specific objectives were to analyze the understanding that professionals have about the subject, and their specialized role and view of the world, how they are building methods to confront this new demand in their daily work. For being a pioneer on the topic of sustainability in the Brazilian scenario, we choose Banco Santander as the experimental field of research. We analyzed their discourse, their practices, their consistency and the view of people interviewed. The subjects were the Bank's three social workers who responded to a semi-structured interview, with a tape recorder to ensure the confidentiality of information that was provided, responding to questions in the workplace. It was found that the institution requires the expertise of these professionals in regards to the actions related to the social support, but it was evident that from the perspective of the researched subjects, this question does not appear so clearly, which indicates a gap in the handling between theory and practice, in the professional exercise of the new demand in question